2012
DOI: 10.1029/2012jd018015
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the number of extreme daily events out to a decade ahead

Abstract: [1] The predictability of daily temperature and precipitation extremes is assessed out to a decade ahead using the Met Office Decadal Prediction System. Extremes are defined using a simple percentile based counting method applied to daily gridded observation data sets and corresponding model forecasts. We investigate moderate extremes, with a 10% probability of occurrence, ensuring they are frequent enough for robust skill analysis while having sizable impacts. We quantify the predictability of extremes, asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 61 publications
6
36
1
Order By: Relevance
“…These results highlights that the potential for using seasonal forecasts as a tool to predict intense precipitation events with a few months in advance is fairly limited for this region. The results presented are broadly consistent with a similar analysis performed by Eade et al (Eade et al, 2012) using the UK Met Office system. These analogies further corroborate the indication that reliable forecasting of intense rainfall on seasonal timescales are still a challenge for state-of-the-art seasonal prediction systems (for additional details see ).…”
Section: Discussion On Climate Products: How Needs Have Been Addressedsupporting
confidence: 82%
“…These results highlights that the potential for using seasonal forecasts as a tool to predict intense precipitation events with a few months in advance is fairly limited for this region. The results presented are broadly consistent with a similar analysis performed by Eade et al (Eade et al, 2012) using the UK Met Office system. These analogies further corroborate the indication that reliable forecasting of intense rainfall on seasonal timescales are still a challenge for state-of-the-art seasonal prediction systems (for additional details see ).…”
Section: Discussion On Climate Products: How Needs Have Been Addressedsupporting
confidence: 82%
“…It is still possible to obtain skillful predictions for more moderate extremes for the UK region, as demonstrated by H13 and Eade et al (2012).…”
Section: Discussionmentioning
confidence: 97%
“…The summer season was the most skillful in the northern hemisphere. A recent study by Eade et al (2012) demonstrated significantly skillful predictions of moderate (1 in 10) temperature extremes on decadal timescales, especially for multi-year periods. These assessments of skill were performed using the Spearman rank correlation coefficient and standardised root mean square error.…”
Section: Introductionmentioning
confidence: 99%
“…Modest multi-year-lead skill improvement for surface temperature over the continents surrounding the Atlantic is present in some systems, particularly over Western Europe and North/Central America, but the improvement varies with season and seems most evident as a reduction of error rather than enhancement of correlation [123, 125, 127, 130•]. At least one study reports modest but significant skill in predicting temperature and precipitation climate extremes over North America and Europe at decadal lead times, although most of the skill appears to be due to external forcing rather than initialization [93]. There is also emerging evidence that rainfall over Africa can be predicted.…”
Section: Impacts Over Landmentioning
confidence: 99%
“…Not only does AMOC appear to correlate with seasonal mean climate signals over land but also with (possibly) predictable shifts in surface climate extremes that have the greatest societal impact [92,93]. Furthermore, AMOC-related heat transport through the Nordic Seas is a key predictor of simulated Arctic sea ice extent, and it appears to control low-frequency atmospheric heat transport variability in that region, in line with Bjerknes' compensation hypothesis [4, 37•, 94, 95, 96•, 97•].…”
Section: Foundations Mechanisms Of Decadal To Multi-decadal Atlantic mentioning
confidence: 99%